THE MAIN FACTORS OF THE TERMINATION OF THE LEASE CONTRACT IN ISLAMIC LAW - Erkaev Mamurjon (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
The article entitled "The main factors of the termination of the lease agreement in Islamic law" was covered based on the following topics. In particular, the expiration of the lease agreement. Although the term has not expired, the leased property has been used, as well as it has been damaged beyond use or completely destroyed, and both or one of the parties to the contract has died. At the same time, when there are reasons that prevent the termination of the lease agreement, its term will be extended, and in this case, payment or payment will be given.